Structural Change and New Zealand's Productivity Performance - Meehan, Lisa (New Zealand Productivity Commission, 2014)
Shift-share analysis decomposes aggregate labour productivity growth into a contribution from withinindustry productivity growth and a contribution from employment movements across industries with differing labour productivity levels. Because the role that structural change plays in productivity growth differs with the level of a country’s economic development, this paper focuses on New Zealand in comparison with other OECD countries. New Zealand’s economy-wide labour productivity growth has been lower than most other OECD countries. As in all other OECD countries examined in this paper, the majority of New Zealand’s labour productivity growth since the early 1990s has come from within-industry productivity growth. Like most other OECD countries, New Zealand has experienced productivity-detracting structural change with employment moving towards industries with below-average levels of labour productivity. In aggregate, New Zealand’s poor labour productivity growth compared with other OECD countries reflects both below-average performance of its within-industry productivity growth and a larger employment shifting towards low-productivity industries. Although the structural change component is a relatively smaller part of overall labour productivity growth, New Zealand’s structural change effect was further behind the OECD average structural change effect than its within-industry productivity growth. New Zealand’s comparatively large negative structural change was due to small differences in employment share changes and relative labour productivity levels in a few industries. Industries that were undergoing significant reforms during the 1990s were the main culprits, with larger employment movements away from high labour productivity industries such as electricity, gas & water and transport, storage & communications in New Zealand than other OECD countries. These differences highlight some of the limitations of shift-share analysis that may be particularly acute during times of reform. For example, the assumption that the average and marginal productivity in an industry are equivalent may result in an overestimation of the negative contribution of structural change. As a small open economy, New Zealand could, in principle, increase output in high-productivity industries through exporting. In practice, New Zealand’s propensity to export is low compared with other small, open economies and this export-led employment shift has not occurred. The shift-share analysis presented in this paper is a first step in understanding the role of resource reallocation in productivity growth in New Zealand. In interpreting the results of this paper it is important to note that shift-share analysis is a descriptive tool to look at high-level structural change. Taken in isolation, it does not provide information on the drivers and dynamics of resource reallocation, nor does it necessarily indicate the mis-allocation of resources. Firm-level data offers the opportunity to explore these issues further.